ANALISIS PELAKSANAAN TABUNGAN HAJI DAN UMROH (TAHAROH) DENGAN AKAD MUDHARABAH PADA BANK KALBAR SYARIAH CABANG SAMBAS - Melati (Sebi : Studi Ekonomi dan Bisnis Islam, 2023)
This research, including qualitative research with a descriptive character, namely where researchers get data from observations, interviews and documentation on the implementation of Hajj and Umrah savings products with a mudharabah agreement carried out by researchers who come directly to Bank Kalbar Syariah Sambas Branch. The results of this study show that the Taharoh Savings Product with the Mudharabah Agreement at Bank Kalbar Syariah Sambas Branch is a fund savings product using the Mudharabah contract (profit sharing) intended for individual customers to pay in installments for Hajj or Umrah fees. The implementation of Taharoh savings products at Bank Kalbar Syariah Sambas Branch using the Mudharabah contract is in accordance with DSN fatwa No. 02 / DSN-MUI / IV / 2000 dated May 12, 2000 that savings that are justified according to sharia principles, namely wadiah savings and mudharabah savings, where this Taharoh savings uses the mudharabah contract the customer acts as a shahibul maal or fund owner, and the bank acts as a mudharib or fund manager. Here the customer has acted as a shahibul maal because the customer has deposited his funds with the bank and the bank itself has also acted as a mudharib , namely as a fund manager and gets profit sharing in accordance with existing provisions.